2018
DOI: 10.1155/2018/2570940
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Different Cattle Breeds to the Infestation of Cattle Ticks Amblyomma variegatum, Rhipicephalus microplus, and Hyalomma spp. on the Natural Pastures of Opkara Farm, Benin

Abstract: A study was carried out on the Opkara (Benin) cattle farm on 64 cattle of four different breeds (16 individuals per breed) from June to December 2016. During this study, three tick species were found in different numbers, Amblyomma variegatum (732), Rhipicephalus microplus (8079), and Hyalomma spp. (208), with parasitic intensity of 11.90, 126.23, and 3.25, respectively. The interracial comparison of the tick infestation between the cattle showed a significant difference (P < 0.001). However, Girolando was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…According to Yessinou et al. (2018), calves are less infested than adult cattle by ticks. However AL‐Hosary et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Yessinou et al. (2018), calves are less infested than adult cattle by ticks. However AL‐Hosary et al.…”
Section: Discussionmentioning
confidence: 99%
“…According toYessinou et al (2018), calves are less infested than adult cattle by ticks. However AL-Hosary et al(2018) reported that cattle aged less than 1 year were more susceptible to infection by T. annulata (83%; 400/480).…”
mentioning
confidence: 99%
“…However, Flach et al(1995) did not observe any relation between immature tick burdens and sex of the cattle hosts. This difference is possibly attributed to the body size and the different quantities of attractive chemicals such as carbon dioxides (Donzé et al, 2004) or genetic factors of the host (Yessinou et al, 2018). The amount of carbon dioxide (CO 2 ) emitted is the first deciding factor to attract the ticks to their hosts (Wanzala et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In Sudanese cattle, the highest rates of infection have been observed in cross breeds, compared to endogenous ones, as they seemed to be very susceptible to tick infestation (89). Relative resistance of native breeds to tick infestation has often been described in relation to distinct patterns of transmission for several tick-borne pathogens (100)(101)(102). However, concerning CCHFV, significant differences were not systematically highlighted, even within the same country (35), and in some cases the tendency was just the opposite (88).…”
Section: Factors That May Promote Cchfv Enzootic Transmission In Fran...mentioning
confidence: 99%